Elevated Temperature Wear Behavior of AZ91 Magnesium Alloy After Micro-Arc Oxidation in Single and Dual Phase Electrolytes - Vanli, Ali Serdar; Muhaffel, Faiz; Kaba, Mertcan; Selvi, Ekin; Baydoğan, Murat (ASME International, 2023)
Abstract Low wear resistance of AZ91 alloy is the main factor limiting its more common use in industrial applications. Therefore, the micro-arc oxidation (MAO) process is mostly applied to the alloy to improve its wear resistance at room temperature (RT). However, the effect of the MAO coating on the wear behavior at elevated temperatures was investigated in limited works. In this study, the MAO process was performed on an AZ91 alloy in single-phase (silicate-containing) and dual-phase (aluminate + phosphate containing) electrolytes, and its wear behavior was investigated at both RT and 200 °C compared to the bare alloy. The results showed that the wear resistance of the alloy could be significantly improved both at RT and 200 °C, and the silicate-based electrolyte provided a better wear resistance at both temperatures. The results also showed that the dominant wear mechanism was oxidation for the bare alloy, and brittle fracture for the MAO-treated alloys.